Feasibility of graphene-enhanced strength in sanitary ceramics - Sherif, Ziyad; Patsavellas, John; Salonitis, Konstantinos (Springer, 2025)
In the competitive production of sanitary ceramics (SCs), fractures during the drying and handling stages significantly contribute to production waste. This study explores the incorporation of graphene, known for its exceptional mechanical properties, to enhance the strength and reduce waste in SCs. Utilising a modified slip casting process, graphene was introduced into Vitreous China (VC) and Fine Fireclay (FFC) ceramics through two methods representing two points of possible graphene inclusion along the production process: An earlier inclusion stage, which was examined by adding graphene solution into ceramic powder to create slip (powder-solution) and a later stage represented by graphene solution added to a readymade slip (solution-solution). The results demonstrated that the solution method significantly improved the mechanical strength of VC, achieving a 12% increase at 1 g graphene inclusion, while the powder method caused a decline in strength due to slip flocculation. FFC showed consistent strength improvements with both methods, with an average increase of 7% at 1 g graphene inclusion. Although the potential for graphene-enhanced ceramics is promising, further research is needed to quantify material savings, evaluate cost-effectiveness, and optimise the integration process for industrial-scale production.
TMS 2025: Annual Meeting & Exhibition, 23-27 March, Las Vegas, NV, USA